Communication Strategies of Gaming Streamers on YouTube Vertical Live: A New Media Perspective - Yudha, Reza Praditya; Pratama, Fajar Januar (Journal Commedies, 2025)
This study investigates the underexplored area of communication strategies in YouTube Vertical Live, focusing on gaming streamers and their real-time audience engagement. While prior research on live streaming often addresses technical aspects or horizontal formats, this study emphasizes the communicative dynamics unique to the vertical format—an emerging trend shaped by mobile-first viewing habits. Grounded in New Media theory, the research employs a qualitative design with in-depth interviews and live session observations of six active gaming streamers. The analysis reveals a distinct set of strategies that leverage the vertical interface: adaptive micro-interactions tailored to instantaneous audience feedback, integration of mobile-optimized interactive features to sustain participation, and strategic persona management to reinforce streamer identity. These findings demonstrate that the vertical format not only reshapes audience accessibility but also redefines parasocial interaction and community-building practices in digital spaces. The study’s novelty lies in its identification of format-specific communication strategies that extend existing New Media discourse, offering both theoretical enrichment and practical implications for content creators and platform developers aiming to maximize engagement in mobile-dominated environments.